"Crossing the Rubicon": Understanding Chinese EFL students' volitional process underlying in-class participation with the theory of planned behaviour. Issue 3 (19th May 2017) - Girardelli, Davide; Patel, Vijay K.; Martins-Shannon, Janine
ABSTRACT: An extended model based on the theory of planned behaviour (TPB) was used to study Chinese English as a foreign language (EFL) students' in-class participation. The model included the core TPB constructs (behavioural intentions, attitudes, subjective norms, and perceived behavioural control/self-efficacy) and 2 additional constructs (foreign language classroom anxiety and face-saving) frequently discussed in the literature about Chinese EFL classroom dynamics. A total of 199 Chinese students enrolled in a Sino-American international branch campus were surveyed. The results of a partial least squares (PLS) path modelling analysis revealed that attitudes, subjective norms, perceived behavioural control/self-efficacy, and face-saving explained 46% of the variance in intentions to participate in English in class. Perceived behavioural control/self-efficacy fully mediated the negative indirect effect of foreign language classroom anxiety on intentions. Pedagogical implications and future directions are discussed for implementation purposes.